PECULIARITIES OF THE DEVELOPMENT OF AIR TRANSPORT IN THE ENERGY ASPECT IN THE CONTEXT OF THE POST-WAR RECONSTRUCTION OF UKRAINE - BOIKO, SERGEY; VYSHNEVSʹKYY, SVIATOSLAV; SHOKAREV, DMYTRO; POLISHCHUK, PETRO; GVOZDIK, STANISLAV (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article emphasizes that the question of researching the place of air transport in the aspect of multimodal transportation in the aspect of the post-war reconstruction of Ukraine is relevant. An analysis of the pre-war dynamics of the development of the transport industry of Ukraine is presented, which showed the insufficient level of development of the transport infrastructure and the organization of transport operations for both the transit country. Directions and approaches to the implementation of elements of a multimodal transport system using air transport are presented. It is proposed for further implementation on the territory of Ukraine, the schemes of multimodal transportation with the involvement of air transport, which are popular in the world practice. The proposed directions for the use of air transport in relation to cargo transportation in the aspect of multimodal transportation in the conditions of Ukraine have been determined. The study identifies the peculiarities of the integration of air transport into the transport system during the post-war reconstruction of Ukraine. For the development of aviation transport in the context of the development of transportation on the territory of Ukraine, it is necessary first of all to determine the strategic directions of the post-war development of the transport industry of Ukraine and potential resource opportunities for their solution. A method of increasing the energy efficiency and reliability of the power supply of aviation enterprises is proposed, which will allow performing a high-quality reconfiguration of the existing energy networks of aviation enterprises and performing a high-quality design of new modern infrastructure networks of the aviation industry.
Keywords: aviation enterprises; multimodal transportation; post-war recovery of Ukraine; sources of distributed generation